1851 Pa. Laws 382, No. 239, § 4. - (:unkn) unknown (General Publisher, 1851)
That any person who shall willfully and maliciously carry any pistol, gun, dirk knife, slung shot, or deadly weapon in said borough of York, shall be deemed guilty of a felony
--
Keywords: GOING ARMED